Health status assessed by physiological parameters and pathogen tests in kelp gulls (Larus dominicanus) feeding on an urban sanitary landfill - Adami, Miguel Angel (2021)
Kelp gulls (Larus dominicanus) are marine seabirds with generalist and opportunistic feeding habits, which allow them to take advantage of the urban waste. However, this food usually contains toxic substances and contaminated food that could influence their health condition. To assess the health of kelp gulls that feed of these types of food, we obtained values of diverse biochemical parameters, plasmatic enzymes and pathogenic bacteria of kelp gulls on an urban landfill in Patagonia, Argentina. Values of glucose obtained were similar than those previously reported for this species when using fishery discards at a closer site in Patagonia and for other species of gulls in the literature. However, the average of total proteins, triglycerides and cholesterol showed lower values than those reported for kelp gulls in general and other species of gulls, which could indicate a diet with a low supply of protein and fat resulting of the ingest of urban domestic food. Except for alanine transaminase that showed lower values, the lactate dehydrogenase, alkaline phosphatase, and aspartate transaminase were higher than those previously reported for other gull species. All the enzymes are involved in the cellular metabolism, and taken together, plus other physiological parameters, they can inform about the correct function of organs and tissues and their variations reflect hepatic, myocardium and tissue diseases, damage or trauma. Although, we expected that gulls feeding on urban waste showed presence of enteropathogenic bacteria that are commonly associated to the human, except for Escherichia coli that were present in 7 gulls out of the 35 sampled, the rest of bacteria tested Salmonella sp., Shigella sp., and Corynebacterium sp. were absent. These data constitute the first physiological report for the species at urban sanitary landfills of Patagonia Argentina.